Calibration and survey of AMANDA with the SPASE detectors - Ahrens, J.; Bai, X.; Boeser, Sebastian; Silvestri, A.; Solarz, M.; Spiczak, G. M.; Spiering, C.; Stamatikos, M.; Stanev, T.; Steele, D.; Steffen, P.; Stokstad, R. G.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2004)
We report on the analysis of air showers observed in coincidence by the Antarctic Muon and Neutrino detector array (AMANDA-B10) and the South Pole Air Shower Experiment (SPASE-1 and SPASE-2). We discuss the use of coincident events for calibration and survey of the deep AMANDA detector as well as the response of AMANDA to muon bundles. This analysis uses data taken during 1997 when both SPASE-1 and SPASE-2 were in operation to provide a stereo view of AMANDA.